A dictionary of medical terms in Galen - Durling, Richard J. (Studies in Ancient Medicine, 1993)
Galen (2nd century A.D.), after Hippocrates the most distinguished physician of antiquity, has left us numerous medical works to which no complete Greek-English dictionary or concordance was available until now. This is a dictionary of ancient Greek medical terms as culled from Galen's voluminous works, covering all medical fields: diet, drugs and surgery. It contains approximately 3,000 Greek words and 119,000 citations. Particularly rich is the vocabulary of plant names, which sometimes defy identification. Dealing with terms from the fields of anatomy, physiology, pathology, pharmacy and surgery this book is essential for the study of medical Greek and will be of interest to both historians of ancient medicine and to classical philologists.